Unravelling the potential of citrus essential oils derived from citrus processing as an alternative antimicrobial feed additive in pigs - Sinche Ambrosio, Carmen Milagros (2020)
Citrus is the most grow fruit around the world and essential oils (EOs) are the main by- product of Citrus-juice processing industries. Lately, EOs have emerged as a promising alternative to antibiotic use in pig production due to their antimicrobial properties. This as a result of the full restriction of antibiotics\' use as feed additive by the European Union since 2016 to counter the increase of antibiotic resistance in animals and humans. Due to the vast availability of citrus EOs in the global market, from a practical standpoint, their application in pig feed could turn interesting and financially feasible. Thus, the aim of this thesis was to unravel the selective antibacterial activity of commercial citrus EOs, as well as their chemical composition related to this activity, targeting citrus EOs\' potential application as an alternative to antibiotics in pig feed. This thesis is divided into five studies, of which the three first studies investigated the in vitro selective antibacterial activity of six commercial citrus EOs, the possible mechanism of action underlying citrus EOs\' selective activity and the chemical composition to unravel citrus EOs\' compounds involved in conferring that selective antibacterial performance. The next study was related to the microencapsulation of a citrus EO using a modified starch-chitosan matrix technique by spray-drying. Physical properties, morphology and antimicrobial activity of the citrus EO microcapsules were evaluated. In the last study, the effect of a microencapsulated citrus EO on pig gut microbiota using a stage of art in vitro fermentation was studied. The result of the present thesis showed the potential of selective antibacterial activity of citrus EOs, that is, a stronger antibacterial effect on pathogenic bacteria than beneficial bacteria by causing higher disturbances of the normal growth kinetics of pathogenic bacteria than beneficial bacteria. The probable mechanism related to the selective antibacterial action of a citrus EO can be described as altering more remarkably the permeability and integrity of the cytoplasmic membrane as well as the external structure of a pathogenic bacterium than a beneficial bacterium. The characterization of the chemical composition of citrus EOs allowed to infer that minor compounds present in these EOs would be involved in conferring their selective antibacterial activity, these would be mainly oxygenated monoterpenes such as carvone, cis-carveol, trans,-carveol, cis-p-Mentha-2,8-dien-1-ol and trans-p-Mentha-2,8-dien-1-ol. In addition, on the basis of an in vitro fermentation set-up, results showed that a microencapsulated citrus EO shifted pig gut microbiota in a way that reduced ileal and colonic diversity and altered their composition. Therefore, this thesis provides new information about the antimicrobial effect of citrus EOs as a potential alternative to antibiotics in pig production.